Antimicrobial activity of Malaysian rainforest crude plant extract and purified methyl gallate products from glochidion superbum against MRSA isolates - Ahmed, Mohammed Dahiru (Kulliyyah of Medicine, International Islamic University Malaysia, 2016)
Methicillin resistant Staphylococcus aureus (MRSA) has been increasingly arising in both hospital and community acquired infections. Besides that, reported resistance of the organism against many of the current and new alternative orthodox drugs is escalating worldwide. Therefore, the search for new drugs from plants' phytochemicals is urgently needed to reduce the burden of MRSA globally. Plants have been known in folk medicine, and as prominent source in drug discovery. Thus in this study, Glochidion superbum's leaves and stem extracts, alongside four other plants'crude extracts ( two leaves extract, roots and stem extracts from Renellia elleptica and Uncaria acida respectively) were screened for antimicrobial activity against four reference bacterial strains by disc diffusion method (p <0.05). Furthermore, Glochidion superbum methanol leaves' extract was fractionated, and tested on two reference bacterial strains. The most active fraction was further purified and a phenolic compound was obtained, as 3,4,5-trihydroxybenzoate (methyl gallate), that was inhibitory to three hospital isolates (p < 0.05) of MRSA both in qualitative disc diffusion test (>20 mm inhibition zone) and in quantitative broth dilution assay (MIC 50-100 µg/mL). The phytochemical properties and chemical structure of the isolate was elucidated by spectroscopic analysis such as ultraviolate, infrared, (1H & 13C)-nuclear magnetic resonance spectroscopy and mass spectroscopy were carried out to characterise the compound. In conclusion, although methyl gallate was isolated from other plants, this study is the first to report its isolation from Glochidion superbum.